Ritme Skank di Pulau Pesta: Keterlibatan Komunitas Reggae dalam Pengembangan Wisata Gili Trawangan - Parama, I Dewa Made Satya; Nasrullah, Arif; Rahmani Hakim, Latifa Dinar (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
The Gili Trawangan in West Nusa Tenggara is now also known as Party Island because there is a variety of nightlife that tourists can enjoy. Reggae is a popular music and is often played amidst the hustle and bustle of tourists. This research seeks to understand how reggae music, which is synonymous with culture, religious movements, social activism and resistance, is mobilized to become a resource for producing musical scenes and performances as a form of participation in tourism development. The research method used is a qualitative research method with a phenomenological approach. The main data was obtained through in-depth interviews with 3 reggae musicians, bar managers and tourists. The results of this research found that the beginnings of reggae music on Gili Trawangan were influenced by the figure of Bob Marley, the popularity of the song Welcome to My Paradise and the typical small island atmosphere that supported reggae's connection with its birthplace in the Caribbean islands, Jamaica. Apart from that, this research found that the growth of reggae music is very dependent on the meaning of the music, the creation of space for expression, the characteristics of tourists and adaptive strategies.